Logos sebagai Titik Temu Teologi dan Filsafat: Kajian Eksegesis Biblikal atas Yohanes 1:1 dalam Dialog dengan Filsafat Stoa - Purwonugroho, Daniel Pesah (Sekolah Tinggi Teologi Torsina Surakarta, 2025)
This paper aims to find theological and philosophical common ground regarding Logos through a biblical exegesis of John 1:1 in dialogue with Stoic philosophy. Logos is a theological concept in the Gospel of John. Logos in the Christian faith highlights the existence of Jesus Christ before creation and the ontological connection of Jesus Christ as God. In addition, Logos in the Christian faith affirms a divine entity that actively shapes the universe. At the same time, Logos is a crucial Stoic term that affirms a rational principle of the cosmos. Logos in Stoic philosophy is regarded as an active force that guides the universe. Logos is also a manifestation of orderly energy that impacts existence. Through a descriptive qualitative approach, it was found that there is a theological and philosophical meeting point regarding the term Logos. This meeting point opens up a space for deep dialogue between the Christian faith and Stoic philosophy. This convergence does not obscure the uniqueness of the Christian faith. Rather, it converges on Jesus Christ as the fulfillment of divine revelation. This paper offers a dialogical approach to the relationship between biblical exegesis and Stoic philosophy. Abstrak Tulisan ini bertujuan untuk mencari titik temu teologis dan filosofis mengenai Logos melalui kajian eksegesis biblikal atas Yohanes 1:1 dalam dialog dengan Filsafat Stoa. Logos adalah konsep teologis dalam Injil Yohanes. Logos dalam iman Kristen menyoroti keberadaan Yesus Kristus sebelum penciptaan dan keterkaitan ontologis Yesus Kristus sebagai Tuhan. Selian itu, Logos dalam iman Kristen menegaskan sebuah entitas ilahi yang berperan aktif dalam membentuk alam semesta. Di saat yang sama,